Effectiveness of Tuberculosis Directly Observed Treatment, Short Course in Saiburi District of Pattani Province in the 9th National Health Development Plan, 2002-2006 - ทางรัตนสุวรรณ ภัททิรา (Disease Control Journal, 2007)
Tuberculosis was one of common re-merging communicable disease which remained and became an important public health problem in Thailand. The Crown Prince Saiburi Hospital had provided treatment of tuberculosis patients by implementation of the DOTS strategy during the 9th National Health Development Plan, 2002-2006. This research study focused on trends in detection of new sputum positive tuberculosis patients, together with studying characteristic trends of sputum positive tuberculosis patients and results of their treatment by the implementation of the DOTS strategy. The method of descriptive and retrospective study was used for collection datas of all sputum positive patients from 2002-2006, whose DOTS strategy were supervised by family members. Overall results revealed increasing trends in morbidity rates from 31.30, 50.28, 60.87, 34.10 and 61.80 per 100,000 population respectively. Majority of them were male and aging group. There were increasing trends of developing disease among working and active reproductive ages. Sputum conversion rate after completion of intensive treatment were found with better trends from 73.68, 70.96, 81.57, 81.48 to 79.48 percent respectively. In addition, there were better trends of the overall treatment success rate of 52.63, 63.73, 78.94, 77.77 and 76.91 percent respectively. However, such treatment success rates were still lower than 85 percent standard target of the national TB program. Reasons for such lower achievement were mainly from insurgents in the area which became more violent and had direct impacts on both health staffs as service providers and TB patients as service recipients. These impacts, therefore, eventually resulted in higher defaulter rate and mortality rate. Majority of defaulters were older age group who suffered from diabetis mellitus and emphysema. Died cases were almost from HIV infected persons. TB patients known to be HIV-infected during 2002-2006 were 15.78, 12.90, 14.82, 14.70 and 10.25 percent respectively. The author had made recommendations to provide more effective counseling and blood screening for HIV infected to every TB cases, in order to provide prompt anti-viral treatment to reduce mortality rate. Further recommendations were also made to increase participation of health core groups, Islamic leaders and other relating volunteers in the implementation of the DOT strategy in order to increasing their effectiveness.